Synthesis, Characterization and Aplication of TiO2 Alumina Pillared Montmorillonite Photocatalyst - Iwan Sumarlan, Is Fatimah, Karna Wijaya (EKSAKTA: Journal of Sciences and Data Analysis, 2013)
Dispersion of TiO2 on montmorillonite pillared aluminium has been done successfully. The photocatalyst were prepared by intercalation of Al13 onto natural montmorillonite and then calcined at 500oC. Titania dispersion onto aluminium pillared montmorillonite was carried out by impregnation method at the theoritic concentration of 0.4, 0.8, 1 and 3% titania. The photocatalyst then characterized by XRD, porosimetry, SEM and Diffuse Reflectance Visible methods. Results of characterization showed that the basal spacing and specific surface area as well as total pore volume were decreased after dispersion of TiO2 on PILM, meanwhile SEM image exhibited that beside in the pores of PILM, the TiO2 was also dispersed on the surface of PILM. DR UV characterization result indicated that the band gap of TiO2 dispersed PILM for Ti/PILM 0,8%, Ti/PILM 1% and Ti/PILM 3% was 3.66, 3.19 and 3.19 eV respectively. Photodegradation optimum of methyl orange was found to be at Ti/PILM 1%Keywords : montmorillonite, pillarization, photocatalyst, methyl orange, TiO2